Rationale for heparin treatment of colon cancer - Zacharski, L. R.; Ornstein, D. L. (Hämostaseologie, 2000)
It is widely known that the systemic blood coagulation mechanism is often activated in malignancy, leading to an increased incidence of vascular thromboses in patients with cancer. It is not widely appreciated, however, that products of the coagulation mechanism may also support tumor growth and dissemination. Interest in this approach to cancer therapy has surged recently because of mounting evidence that the familiar anticoagulant drug, heparin, may impede tumor progression. Heparin has the capacity to modify angiogenesis, growth factor and protease activity, immune function, cell proliferation and gene expression in ways that may block malignant dissemination. Clinical trials in which heparin has been administered to a broad spectrum of patients to prevent or treat thrombosis have unexpectedly shown improvement in survival in the subset of patients with malignancy entered to these studies. Meta-analyses of clinical trials comparing unfractionated (UF) versus low molecular weight (LMW) heparin treating venous thromboembolism suggest that there may be substantial improvement in cancer outcome in patients with malignancy randomized to receive LMW heparin. These findings provide a rationale for definitive clinical trials of LMW heparin in cancer, and the results of several such studies that are currently underway are awaited with interest.
Keywords: Cancer; anticoagulant treatment; heparin